Analysis of risk factors and application of risk management strategies in hemodialysis patients complicated with heart failure - Guiren Hou; Sai Chen (Frontiers in Cardiovascular Medicine)
BackgroundHeart failure (HF) is a common and serious complication in maintenance hemodialysis (MHD) patients, significantly affecting their prognosis and quality of life. This study aims to identify risk factors for HF and evaluate targeted, risk-based nursing interventions.MethodsA total of 170 MHD patients admitted between January 2022 and January 2024 were divided into HF (n = 80) and non-HF groups (n = 90) based on the presence or absence of HF. Risk factors were analyzed using univariate and multivariate logistic regression. Subsequently, 80 HF patients were randomized to standard group (n = 40) or study group receiving targeted risk management strategies (n = 40). The intervention lasted 8 weeks and included comprehensive nursing measures based on individualized risk profiles. Outcome measures included Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), complications, quality of life (SF-36), and nursing satisfaction.ResultsUnivariate analysis identified age (OR = 1.076), dialysis duration (OR = 1.054), hypertension (OR = 3.391), diabetes (OR = 2.874), coronary heart disease (OR = 3.115), smoking history (OR = 1.976), HbA1c (OR = 18.675), and C-reactive protein (CRP; OR = 1.466) as risk factors for HF in MHD patients (P < 0.05). Multivariate logistic regression analysis confirmed age (OR = 1.079), HbA1c (OR = 20.371), and CRP (OR = 1.542) as independent risk factors. After management, compared with the standard group, the study group showed significant reductions in SAS and SDS scores and complication incidence (P < 0.05). The quality of life and nursing satisfaction significantly improved in the study group (P < 0.05).ConclusionAge, hyperglycemia, inflammation, and comorbidities (hypertension, diabetes, coronary heart disease) independently increase HF risk in MHD patients. Targeted risk management reduces psychological distress, complications, and enhances care outcomes.